Hemorrhagic Cholecystitis. A Challenge for the General Surgeon - Eduardo, Sánchez Martínez Gustavo; Ramón, Szymanski Florencia Luis; Emmanuel, Muñiz Calderón Mario; Sofía, Juárez Mendoza Diana (Archives of Clinical and Medical Case Reports, 2024)
Hemorrhagic cholecystitis is a complication of acute cholecystitis that been seen rarely. However, shows high mortality once the first symptoms are detected. Its diagnosis is a big challenge, as the main signs are often confused or dismissed guiding at more common clinical diagnosis. The case of a 35-year-old male is presented, with the principal symptoms described below: 3 days of abdominal pain, with evolution and discomfort in the right iliac fossa, which led to carry out a medical review that resulted in an emergency open appendectomy, where hemoperitoneum and cecal appendix were found without pathological data, so it was decided to approach by midline finding the origin of the bleeding in the gallbladder. Hemorrhage, due to inflammatory changes, causes ulceration of the mucosa and necrosis, distends the gallbladder and, finally, causes its rupture and hemoperitoneum. The most frequent site where a perforation appear is in the bottom of gallbladder, due to the inadequate vascular supply, deriving in lack of nutrients and a slowest repair process than the other parts of the organ. In most cases the treatment that exhibit the best results is the cholecystectomy.